Apical leakage after root canal filling with an experimental calcium hydroxide gutta-percha point - Holland, Roberto [UNESP]; Murata, Sueli Satomi [UNESP]; Dezan Junior, Eloi [UNESP]; Garlipp, Oswaldo [UNESP] (Elsevier, 1996)
This study was an in vitro analysis of the apical seal of root canals filled with an experimental calcium hydroxide gutta-percha point. One hundred and ten recently extracted human permanent teeth with a single root were used. The root canals were biomechanically prepared, and some received a dressing of calcium hydroxide for 7 days. Root canals not dressed were filled by the lateral condensation technique with either regular gutta-percha or calcium hydroxide gutta-percha points. The dressed root canals were filled with the same sealers and regular gutta-percha points. The specimens were placed into a 2% methylene blue dye solution under vacuum, and the apical leakage was linearly evaluated. The experimental groups with calcium hydroxide dressing and the one with calcium hydroxide gutta-percha points exhibited significantly (p < 0.05) less leakage than the groups filled with regular gutta-percha points. The results obtained indicated that calcium hydroxide guttapercha points produced an improvement in the apical sealing quality of the root canal filling. Copyright © 1996 by The American Association of Endodontists.
Keywords: biomedical and dental materials; calcium hydroxide; Grossman sealer; gutta percha; root canal filling material; zinc oxide eugenol; analysis of variance; comparative study; endodontics; human; methodology; tooth disease; Analysis of Variance; Calcium Hydroxide; Dental Leakage; Gutta-Percha; Humans; Root Canal Filling Materials; Root Canal Irrigants; Root Canal Obturation; Zinc Oxide-Eugenol Cement